The Evolution of Customer Engagement in the Digital Era for Business: A Review and Future Research Agenda - Rasul, T.; Nair, S.; Palamidovska -sterjadovska, Nikolina; Ladeira, W. J.; Santini, F. d. O., & Elgammal, I. (Taylor & Francis, 2024)
This study explores the evolution of customer engagement in the digital era for businesses, a crucial concept in today’s interconnected marketplace facilitated by a variety of digital platforms. The study identifies a gap in the comprehensive understanding and conceptualisation of digital customer engagement across various social media platforms and mediums. By using a bibliometric analysis approach, this study reviews 547 articles published between 2010 and 2021, offering a holistic view of the existing research landscape. The analysis uncovers four distinct bibliometric clusters representing unique facets of customer engagement: brand engagement, behavioural insights, loyalty dynamics, and relationship dynamics. These clusters provide insights into the multifaceted nature of customer relationships and engagements facilitated by digital platforms. The study concludes by proposing seven future research directions, aiming to guide scholars in exploring uncharted territories in digital customer engagement and its implications for businesses in the digital age.
Keywords: Customer engagement; digital era; bibliometric analysis; bibliographic coupling; research directions